2007
DOI: 10.1159/000104770
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Exercise Impacts on the Rat Hypothalamic-Pituitary-Adrenocortical Axis Mainly at the Adrenal Level

Abstract: Introduction: Evidence is accumulating that the regular performance of exercise is beneficial for stress coping. However, the hypothalamic-pituitary-adrenocortical (HPA) axis of voluntarily exercising rats has never been comprehensively investigated. Methods: Therefore, male Sprague-Dawley rats were given access to a running wheel in their home cage for 4 weeks in which they ran 4–7 km per night. Results: After 4 weeks, the exercising animals showed significantly less body weight gain, less abdominal fat tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
143
7
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(172 citation statements)
references
References 109 publications
18
143
7
1
Order By: Relevance
“…In accordance with this, 2 wk of voluntary wheel running have recently been shown to increase mRNA levels of StAR (25). Alternatively, a recent study has also suggested that enhanced sympathoadrenomedullary activity, found to be associated with exercise training, may positively modulate adrenal sensitivity to ACTH (8). Considering that epinephrine has previously been demonstrated to stimulate adrenocortical steroidogensis and secretion of GCs (8), our study proposes possible target genes on which this increased sympathoadrenomedullary input may be operating.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In accordance with this, 2 wk of voluntary wheel running have recently been shown to increase mRNA levels of StAR (25). Alternatively, a recent study has also suggested that enhanced sympathoadrenomedullary activity, found to be associated with exercise training, may positively modulate adrenal sensitivity to ACTH (8). Considering that epinephrine has previously been demonstrated to stimulate adrenocortical steroidogensis and secretion of GCs (8), our study proposes possible target genes on which this increased sympathoadrenomedullary input may be operating.…”
Section: Discussionsupporting
confidence: 77%
“…This suggests that impaired negative feedback sensitivity is likely not the cause of HPA hyperactivity during the early stages of exercise training. Rather, we and others (8) believe that significant adaptations in the adrenal glands occur with prolonged training, such that adrenal sensitivity to ACTH is enhanced. Indeed, we clearly confirm this hypothesis here, by using a standardized ACTH challenge to show that exercising animals have increased adrenal sensitivity at 2 wk (Fig.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The rat model of exercise has been used extensively to study the physiological effects of physical activity using such exercise modalities as swimming (24, 32), running (20,29,41,49,52), jumping (57), tower climbing (43), rising to an erect bipedal stance (11, 64), and weight lifting (62). The effects of exercise on bone have been widely characterized in the rat.…”
mentioning
confidence: 99%